PENERAPAN ALJABAR LINEAR PADA RANGKAIAN LISTRIK - M. Hizryan Furqan; Philip Maloma Sinaga; Nabila Syakira; Ester yunika purba (Kampus Akademik Publiser, 2026)
Linear algebra is a branch of mathematics that plays an essential role in various engineering fields, particularly in electrical circuit analysis. Complex electrical circuits often produce systems of linear equations that are difficult to solve manually. Therefore, a systematic mathematical approach is required to obtain efficient and accurate solutions. This study aims to examine the application of linear algebra concepts, especially matrices and systems of linear equations, in electrical circuit analysis using mesh and nodal methods. The research method employed is a literature study combined with mathematical analysis of electrical circuit models. The results indicate that the matrix method simplifies the calculation of currents and voltages in electrical circuits and improves the efficiency of solving complex equation systems. Thus, the application of linear algebra provides a significant contribution to simplifying electrical circuit analysis in a systematic and structured manner